Exploring the Relationship between Foreign Investments and Carbon Emission: A Bound Test Analysis for Pakistan - Samreen, H.; Wizarat, S.; Mehdi, Z.; Ahmed, R. (Engineering, Technology & Applied Science Research, 2021)
In this study, the theoretical and empirical effects of foreign investment, openness to trade, urbanization, and economic development on carbon dioxide emission levels (CO2) in Pakistan were examined. Annual time series for 38 years 1970-2018 were utilized. The Auto Regressive Distributed Lag (ARDL) bound test has been used to estimate the model which indicates the presence of cointegration among the variables. Long-run and short-run relationships were observed between Foreign Direct Investment (FDI) and CO2 emission levels revealing that increase in FDI results in increased CO2 emission levels contributing to environmental degradation. This endorses the theory of Pollution Haven Hypothesis (PHH) in the case of Pakistan. To achieve the goal of sustainable economic development, it is imperative to consider the possible negative effects of foreign investment on the environment. The study suggests limiting CO2 emissions by adopting more advanced low carbon technologies to ensure growth and a sustainable environment. Strict implementation of environmental laws for foreign and domestic firms both by defining CO2 emission limits, installation of proper waste management plants, and imposing a pollution tax are crucial steps for the improvement of environmental quality.